Non-culture diagnosis of Chlamydia trachomatis genital infection in sexually active women - Mahmud, NU; Hossain, MA; Nahar, K; Ahmed, GS; Mahmud, C; Paul, SL; Khan, SI; Amin, SR; Nasreen, SA; Ahmed, S; et al. (Mymensingh Medical Journal, 2012)
Mymensingh Med J. 2012 Jan;21(1):8-12 The abstract of this article is available on the PubMed website